Deafened people : adjustment and support - Woodcock, Kathryn Lee, 1956-; Aguayo, Miguel Oswald, 1955- (University of Toronto Press, 2000)
It is estimated that there are currently 1.9 million deafened people living in North America - individuals who could once hear naturally or with amplification but have become deaf and are now unable to rely on hearing to comprehend spoken information. Despite this vast number, until now there have been few books that specifically address the process of adjustment to, and acceptance of, deafness as an adult. Kathryn Woodcock and Miguel Aguayo have addressed that situation with their unique look at deafness in Deafened People: Adjustment and Support. The authors demonstrate that deafness is not merely a medical condition; it is a social disability that affects the individual, the family, the social circle, and the work group. By describing the psychosocial experience of acquired deafness as a process of adjustment, Woodcock and Aguayo demonstrate that acceptance of deafness is a process involving practical, social, and emotional implications. To assist in that process, the authors have provided a guide to self-help techniques of proven value to deafened people. Drawing on their own experiences as deaf professionals, Woodcock and Aguayo explore such questions as how deafness occurs, how relationships (professional and personal) can be affected by progressive deafness, and how and where to find peer support. Section 1 describes the process of adjustment, while section 2 offers a practical guide to a successful method of establishing a self-help support network, with reference to such organizations as the Association of Late-Deafened Adults. Written in a lively, engaging style, the book combines medical background, professional advice, information on resources, and personal examples. Deafened People: Adjustment and Support will be invaluable for medical professionals and lay readers alike.